2018
DOI: 10.1093/milmed/usy231
|View full text |Cite
|
Sign up to set email alerts
|

OEF/OIF/OND Veterans Seeking PTSD Treatment: Perceptions of Partner Involvement in Trauma-Focused Treatment

Abstract: We confirmed that OEF/OIF/OND veterans seeking PTSD treatment experience PTSD-related problems in romantic relationships, low-relationship satisfaction, and relationship satisfaction was positively associated with perceived communication and problem-solving skills. A minority of veterans were interested in involving significant others in their PTSD treatment; however, in the present study, veterans were not given information about the various ways that a romantic partner might be involved in treatment, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…One qualitative study by Snell and Tusaie (2008) found that the most frequently cited reason for seeking treatment was disruptions in relationships with significant others, including ultimatums issued by partners demanding that the veteran get help. Additionally, another study found that among veterans seeking treatment for PTSD, the majority reported current romantic relationship dissatisfaction (Malaktaris et al, 2019). Another study measuring mental health utilization using electronic medical record data found that relationship satisfaction was negatively related to mental health service use; however, PTSD symptom severity was only related to mental health service use at mean and high levels of relationship satisfaction (McGinn et al, 2017).…”
mentioning
confidence: 99%
“…One qualitative study by Snell and Tusaie (2008) found that the most frequently cited reason for seeking treatment was disruptions in relationships with significant others, including ultimatums issued by partners demanding that the veteran get help. Additionally, another study found that among veterans seeking treatment for PTSD, the majority reported current romantic relationship dissatisfaction (Malaktaris et al, 2019). Another study measuring mental health utilization using electronic medical record data found that relationship satisfaction was negatively related to mental health service use; however, PTSD symptom severity was only related to mental health service use at mean and high levels of relationship satisfaction (McGinn et al, 2017).…”
mentioning
confidence: 99%
“…27 Additionally, there is strong evidence from systematic reviews documenting the effectiveness of couples therapies for treating adult PTSD and improving interpersonal relationship problems secondary to PTSD symptoms. 11,12,28 Given the research linking PTSD and relational discord in veteran populations, this finding suggests potential underutilization of trauma-informed family therapy among VHA patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are also consistent with qualitative work that suggests that male veterans often cite difficulties in their significant relationships as a reason for seeking mental health treatment (Snell & Tusaie, 2008). Problems in intimate relationships appear to be a particularly salient motivator for mental health treatment seeking among male veterans with PTSD (Harper et al, 2021; Malaktaris et al, 2019). Men tend to have smaller social networks than women, and disruptions in relationships more negatively impact social networks for men (McLaughlin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, poor intimate relationship functioning (i.e., difficulties with satisfaction, distress, support, and communication) can serve as a motivator for initiating mental health treatment. For example, difficulties in intimate relationships are often cited as a reason for mental health treatment seeking, especially among male veterans with PTSD (Malaktaris et al, 2019; Snell & Tusaie, 2008). However, little research has specifically examined the relationships between PTSD, intimate relationship functioning, and mental health treatment seeking.…”
mentioning
confidence: 99%